IMPLEMENTASI PENDIDIKAN AGAMA HINDU DALAM GEGURITAN BHARATA YUDHA KARANGAN KETUT PUTRU PADA UPACARA PAIBON PANDE - I Ketut Mara Pandeyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Geguritan Bharata Yudha, a classic Balinese literary work, is an epic that not only tells thestory of the great battle between the Pandavas and Kauravas, but is also full of educational value ingeguritan so it is worth researching. The aim of this research is to analyze: 1) The structure ofGeguritan Baharata Yudha Karangan Ketut Putru, 2) Implementation of Hindu Religious EducationValues in Geguritan Bharata Yudha Karangan Ketut Putru at the Paibon Pande Ceremony in PedVillage, 3) Implications of Hindu Religious Education Values in Geguritan Bharata Yudha KaranganKetut Putru Pada Piodalan Paibon Pande in Ped Village. The theories used are: 1) StructuralismTheory, 2) Hermeneutic Theory 3) Functional Theory. Type of qualitative research, data collectiontechniques through observation, interviews and document study. Purposive Sampling InformantDetermination Technique. Based on Qualitative Descriptive Analysis, the results obtained are: 1)The structure of Geguritan Bharata Yudha Karangan Ketut Putru has 2 structures, namely 1) FormalStructure, 2) Narrative Structure, Formal Structure consists of: (1) Literary Code, (2) LanguageStyle, ( 3) Variety of Language, (4) Tembang, Narrative Structure consisting of: (1) Synopsis, (2)Theme, (3) Characters and Characterization, (4) Plot or Plot, (5) Setting, (6) Mandate, and (7)Incidents, 2) Implementation of Hindu Religious Educational Values by Ketut Putru at the PaibonPande Ceremony in Ped Village, including: (1) Implementation of Tattwa (philosophy) EducationalValues, (Widhi Sradha), (2) Implementation of Educational Values Susila (ethics), (3)Implementation of Aesthetic Education Values (beauty), (4) Implementation of Ceremonial EducationValues (rituals), 3) Implications of Hindu Religious Education Values in Geguritan Bharata YudhaKarangan Ketut Putru at the Paibon Pande Ceremony in Ped Village, which includes: (1) PolicyImplications, (2) Implications for the younger generation and the older generation, (3) Implicationsof Community Interests in Mageguritan, (4) Cultivating Polite Attitudes and Getting Closer to God.